Stepwise‐refinement for performance: a methodology for many‐core programming. (27th January 2015) - Hijma, P.; van Nieuwpoort, R. V.; Jacobs, C. J. H.; Bal, H. E.
Summary: Many‐core hardware is targeted specifically at obtaining high performance, but reaching high performance is often challenging because hardware‐specific details have to be taken into account. Although there are many programming systems that try to alleviate many‐core programming, some providing a high‐level language, others providing a low‐level language for control, none of these systems have a clear and systematic methodology as a foundation. In this article, we propose stepwise‐refinement for performance : a novel, clear, and structured methodology for obtaining high performance on many‐cores. We present a system that supports this methodology, offers multiple levels of abstraction to provide programmers a trade‐off between high‐level and low‐level programming, and provides programmers detailed performance feedback. We evaluate our methodology with several widely varying compute kernels on two different many‐core architectures: a Graphical Processing Unit (GPU) and the Xeon Phi. We show that our methodology gives insight in the performance, and that in almost all cases, we gain a substantial performance improvement using our methodology. Copyright © 2015 John Wiley & Sons, Ltd.